Tinkering under the Hood: Metabolic Optimisation of CAR-T Cell Therapy - Jenkins, Yasmin (Antibodies (Basel), 2021)
Chimeric antigen receptor (CAR)-T cells are one of the most exciting areas of immunotherapy to date. Clinically available CAR-T cells are used to treat advanced haematological B-cell malignancies with complete remission achieved at around 30–40%. Unfortunately, CAR-T cell success rates are even less impressive when considering a solid tumour. Reasons for this include the paucity of tumour specific targets and greater degree of co-expression on normal tissues. However, there is accumulating evidence that considerable competition for nutrients such as carbohydrates and amino acids within the tumour microenvironment (TME) coupled with immunosuppression result in mitochondrial dysfunction, exhaustion, and subsequent CAR-T cell depletion. In this review, we will examine research avenues being pursued to dissect the various mechanisms contributing to the immunosuppressive TME and outline in vitro strategies currently under investigation that focus on boosting the metabolic program of CAR-T cells as a mechanism to overcome the immunosuppressive TME. Various in vitro and in vivo techniques boost oxidative phosphorylation and mitochondrial fitness in CAR-T cells, resulting in an enhanced central memory T cell compartment and increased anti-tumoural immunity. These include intracellular metabolic enhancers and extracellular in vitro culture optimisation pre-infusion. It is likely that the next generation of CAR-T products will incorporate these elements of metabolic manipulation in CAR-T cell design and manufacture. Given the importance of immunometabolism and T cell function, it is critical that we identify ways to metabolically armour CAR-T cells to overcome the hostile TME and increase clinical efficacy.